Reflections about the curriculum of the so-called LOMLOE from its implementation into the Secondary Education syllabus - Sánchez Liendo, Eduardo (Avances en Supervisión Educativa, 2023)
The curriculum of the so-called LOMLOE introduces a system which, because of being new and challenging, seems to be difficult to teachers in order to elaborate their syllabus. Therefore, this paper intends to look into and to analyze the different elements that form the curriculum, to understand the purpose of each one, to explain their functioning, and to establish how to proceed to put into practice that means the making of the syllabus. The result is a model which tries to illustrate the logic which underlies all the system, to explain the relations between the different elements of the curriculum, and, from that point, to show how to bring together the curricular organisation and the evaluation system within this framework with the ultimate objective of reaching the acquisition of the key competences. Furthermore, the result allows to conclude some positive aspects of the new law whose importante must be highlighted, getting over the controversy they arouse.
Keywords: Educational reform; Educational curriculum; LOMLOE; Syllabus; Evaluation guidelines; Key competences; Evaluation criteria; Essential learning